Prognostic effects of TERT promoter mutations are enhanced by coexistence with BRAF or RAS mutations and strengthen the risk prediction by the ATA or TNM staging system in differentiated thyroid cancer patients. Issue 9 (11th March 2016) - Song, Young Shin; Lim, Jung Ah; Choi, Hoonsung; Won, Jae‐Kyung; Moon, Jae Hoon; Cho, Sun Wook; Lee, Kyu Eun; Park, Young Joo; Yi, Ka Hee; Park, Do Joon; Seo, Jeong‐Sun
Abstract : BACKGROUND: Recent reports suggest that mutations in the promoter of the gene encoding telomerase reverse transcriptase ( TERT ) affect thyroid cancer outcomes. METHODS: In all, 551 patients with differentiated thyroid cancer (DTC) enrolled in this study. The median follow‐up duration was 4.8 years (interquartile range, 3.4‐10.6 years). RESULTS: TERT promoter mutations were detected in 25 DTCs (4.5%): 2.8% in neither BRAF ‐mutated nor RAS ‐mutated tumors, 4.8% in BRAF ‐mutated tumors, and 11.3% in RAS ‐mutated tumors. Moreover, they were frequently observed in American Thyroid Association (ATA) high‐risk and TNM stage III/IV groups (9.1% and 12.9%, respectively). The coexistence of BRAF or RAS with TERT promoter mutations increased aggressive clinicopathologic features, recurrence (hazard ratio [HR] for BRAF, 4.64; 95% confidence interval [CI], 1.42‐15.18; HR for RAS, 5.36; 95% CI, 1.20‐24.02), and mortality (HR for BRAF, 15.13; 95% CI, 1.55‐148.23; HR for RAS, 14.75; 95% CI, 1.30‐167.00), even after adjustments for the age at diagnosis and sex, although the significance was lost after additional adjustments for pathologic characteristics. Furthermore, TERT promoter mutations significantly increased the risk of both recurrence and mortality in the ATA high‐risk (HR for recurrence, 5.79; 95% CI, 2.07‐16.18; HR for mortality, 16.16; 95% CI, 2.10‐124.15) and TNM stage III/IV groups (HR for recurrence, 3.60; 95% CI, 1.19‐10.85; HR for mortality, 9.06; 95% CI, 2.09‐39.26). CONCLUSIONS: The coexistence of BRAF or RAS mutations enhanced the prognostic effects of TERT promoter mutations. Furthermore, TERT promoter mutations strengthened the predictions of mortality and recurrence by the ATA and TNM staging systems, particularly for high‐risk patients with DTC. Cancer 2016;122:1370–1379 . © 2016 American Cancer Society . Abstract : Prognostic effects of telomerase reverse transcriptase ( TERT ) promoter mutations are enhanced by coexistence with BRAF or RAS mutations in differentiated thyroid cancer. Genetic screening for TERT promoter mutations could strengthen the predictions of mortality and recurrence by preexisting staging systems, including the American Thyroid Association and TNM systems, particularly for high‐risk patients.